HARNESSING NANOMEDICINE AND ANTIMICROBIAL PEPTIDES (AMPS) TO COMBAT BACTERIAL INFECTIONS: A NEW FRONTIER (The Research of Medical Science Review, 2025)
Nanomedicine has been one of the most promising fields for bacterial infections over the last few years. This review has mainly focused on the recent advances in nanoparticle-based antibacterial nano-systems with a major focus on antimicrobial peptides. The naturally produced molecules are highly significant in carrying out the innate immune defense in different organisms. However, various concerns such as the proteolytic degradation of the peptides, high costs in the production processes, and various toxicity issues limited the application of AMPs in the clinic. Nanoparticles are a brand-new way to bypass these limitations of AMPs. By using nano-systems, researchers can increase the stability of AMPs and prolong their release time to enhance bioavailability, target specific sites of infections, and thus minimize off-target effects. Nanoparticles are made to have higher binding affinity to AMP and decrease the interaction with host cells, thus, enhancing the therapeutic efficacy of nanoparticles. Hence, nanomedicine could take advantage of the promise of AMPs and overcome some inherent limitations of these biomolecules.